Carving Out Central Europe as a Space of Legal Culture: A Way Out of Peripherality? - Mańko, Rafał; Škop, Martin; Štěpáníková, Markéta (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The aim of the present paper is to contribute to promoting a discourse of Central and Eastern European legal identity, underscoring the legal-cultural bonds of legal cutlure in the region, based on a common past, a common juridico-political mentality and a common present predicament. To this end, the paper posits regarding Central Europe as being a legal family in its own right, distinct both from other legal families in Europe. The paper contends that legal taxonomy is a matter of social construction of reality and has a disciplining function. Considering the ‘death and burial’ of the Socialist Legal Family as the founding myth of Central European regional juridical identity, the paper posits the succession of the former by two coexisting legal families: the Central European and the Eastern European/Eurasian ones. However, the paper does not intend to give definitive answers to the questions of legal taxonomy of the post-Soviet/post-socialist juridical space; its ambition is more moderate – to put forward a number of arguments in favour of a Central European legal family with the intent of destabilising the hegemonic ‘return to Europe’ approach and fostering a discussion of comparatists, legal theorists and socio-legal scientists focused on the problem of legal identity of our region.
Keywords: prawo porównawcze; taksonomia prawna; Europa Środkowa; Środkowoeuropejska Rodzina Prawnicza; Socjalistyczna Rodzina Prawnicza; tożsamość prawna; kultura prawna; tradycja prawna